Impact of crop diversification on livelihood improvement and sustainable land management in Chattogram Hill Tracts of Bangladesh (Journal of Biodiversity Conservation and Bioresource Management, 2021)
The study was conducted at Sorai union of Lama Upazilla under Bandarban district of Chattogram Hill Tracts. It was found that total 19 plant species including bamboos, timbers and fruit crops have been widely cultivated in the area. Among the species five bamboo (Mitinga, Baijja Muli, Borak and Kali), six timbers (Acacia, Eucalyptus, Garjon, Teak, Gamar and Rubber) and eight fruits (Mango, Olive, Papaya, Guava, Coconut, Hog pulm, Orange and Betel nut) were recorded. Bamboo based agro-forestry modules were developed and practiced which produced a very good cropping diversification to sustain the crop productivity, protection of land sliding, soil erosion, water shade and soil fertility in the hill areas. It has been observed that farmers’ have a very good positive attitude and perception in diversified cropping system to get better yields than mono cropping agricultural practice at their home- stead and farm- lands. It has a very good opportunity to make the crop diversification for sustainable production of hill farming and resource management.J. Biodivers. Conserv. Bioresour. Manag. 2020, 6(1): 1-8